The incredible excess entropy in high entropy alloys. (15th July 2019) - Wang, Jianbin; Li, Junjie; Wang, Qing; Wang, Jincheng; Wang, Zhijun; Liu, C.T.
Abstract: The increased excess entropy in face-centered-cubic high entropy alloys is confirmed by quantitatively measuring heat capacities of pure Ni together with equiatomic NiCo, NiCoCr, and NiCoFeCr alloys with increasing configurational entropy. Surprisingly, the incredible excess entropy in the NiCoFeCr alloy can be even up to 0.9R, much larger than that in traditional alloys. The temperature-dependent measurement of the excess entropy indicates the major contribution of lattice vibrations. The excess magnetic entropy dominates in the temperature of 300 to 1000 K. The abnormal excess entropy reveals extraordinary lattice dynamic effects in high entropy alloys, which is a new feature in these alloys. Graphical abstract: The significant excess entropy at lower temperatures and their subtle shifts at high temperatures.Unlabelled Image